A quantitative genetics approach to validate lab- versus field-based behavior in novel environments. (17th June 2021) - Mouchet, Alexia; Dingemanse, Niels J
Abstract: Conclusions about the adaptive nature of repeatable variation in behavior (i.e., "personality") are often derived from laboratory-based assays. However, the expression of genetic variation differs between laboratory and field. Laboratory-based behavior might not predict field-based behavior thus, cross-context validation is required. We estimated the cross-context correlation between behavior expressed by wild great tits ( Parus major ) in established laboratory versus field novel environment assays. Both assays have been used as proxies for "exploration tendency." Behavior in both contexts had similar repeatability (R = 0.35 vs. 0.37) but differed in heritability (h 2 = 0.06 vs. 0.23), implying differences in selection pressures. Unexpectedly, there was no cross-context correlation. Laboratory- and field-based behavior thus reflected expressions of two distinct underlying characters. Post hoc simulations revealed that sampling bias did not explain the lack of correlation. Laboratory-based behavior may reflect fear and exploration, but field-based behavior may reflect escape behavior instead, though other functional interpretations cannot be excluded. Thus, in great tits, activity expressed in laboratory versus field novel environment assays is modulated by multiple quasi-independent characters. The lack of cross-context correlation shown here may also apply to other setups, other repeatable behaviors, and other taxa. Our study thus implies care should be taken in labeling behaviors prior to firm validation studies. Abstract : Personality of wild birds scored using a laboratory test might not predict behavior expressed in the wild. Based on a 10-year dataset, laboratory- and field-based activity in novel environments did not correlate in wild great tit populations ( Parus major ). They thus represented different behaviors. Laboratory-based behavior was largely environmentally determined, while field-based behavior was equally affected by environmental and genetic factors. Activity displayed in two different novel environments likely results from different genetic pathways.